Analisis Produksi Biogas Berdasarkan Bahan Baku Limbah Kotoran Sapi, Serbuk Gergaji, dan Effective Microorganisme-4 (EM4) - Adrianto, Mario Dwi (Jurnal BETA (Biosistem dan Teknik Pertanian); Vol 7 No 2 (2019): September, 2019)
Biogas is an alternative energy made from organic waste. Organic waste which is often used as raw material for biogas is cow dung. Cow manure is used as raw material for biogas because the cellulose content in it is quite high and its availability is relatively large. However, if only one material is used, the optimum C / N ratio will not be achieved. If the optimum C / N ratio is achieved, the gas produced in biogas production will also increase. One way to get the optimum C / N ratio is by adding biogas filling material. In this study, variations in the composition of biogas filling materials were carried out, namely (1) cow dung, (2) cow dung and sawdust, and (3) cow dung, sawdust, and EM4. Of the three variations of this filling material, measurements of temperature, gas pressure, and pH will be carried out. The purpose of this study was to determine the effect of the composition of the biogas mixture on the variables of temperature, gas pressure, and pH. The biogas production process were divided into several stages, such as mixing filling material, inputting filling material into the digester, fermentation process, taking the data of observation, and analyzing the data. The results showed that differences in the composition of biogas raw materials affected the variable temperature and gas pressure. As for pH, the composition of the filling material does not have a significant effect.   Keywords: biogas, cow dung, sawdust, EM4